Islamic Microcredit-based Financing Analysis: A Study of Islamic Banking in the Special Region of Yogyakarta - Manggala Putri, Syah Amelia; Rahayu Firmansyah, Eka Jati; Hayati, Safaah Restuning (AL-FALAH : Journal of Islamic Economics, 2023)
Purpose: The goal of this research is to find out how Sharia banking can overtake financing for MSMEs that are not yet bankable by sticking to prudential banking with a case study: Islamic Banking in the Special Region of YogyakartaDesign/Method/Approach: This is qualitative research using a triangulation method to verify the validity of the data obtained. The research was undertaken at an Islamic bank in the Special Region of Yogyakarta, Indonesia disbursing KUR.Findings: The results of this study are that Islamic banking in the Special Region of Yogyakarta (DIY) applies the 5 CS methods (Character, Capacity, Capital, Collateral, and Condition of Economy) when conducting a financing analysis of their prospective KUR recipient customers.Organally/Value: The method found in this study is beneficial for analyzing unbankable MSMEs. Islamic banks can believe in the ability to pay prospective customers despite the limitations of the data and documents analyzed. This method is beneficial to help unbankable MSMEs to be able to access capital from Islamic banking.Â